65.7k views
5 votes
Write the polynomial as a product: p2q+r2–pqr–pr

2 Answers

2 votes


{p}^(2) q + {r}^(2) - pqr - pr \\ = pq(p - r) - r(p - r) \\ = (pq - r)(p - r)

User Efritz
by
5.1k points
6 votes

Answer:

(p - r)(pq - r)

Explanation:

P = p²q + r² – pqr – pr

Rewrite the equation in descending orders of p and increasing orders of r.

P = p²q - pqr - pr + r²

Factor the first two and the last two terms

P = pq(p - r) - r(p - r)

Remove the common factor

P = (p - r)(pq - r)

User Christopher Scott
by
5.6k points